دراسة تحليلية لخوارزميتي ( MFCCو Endpoint) ومدى تأثيرهما في نسب التعرف على الصوت - الكعدي, دعد (Latakia University Journal -Engineering Sciences Series, 2017)
يشتمل التعرف على الصوت قسمين أساسيين وهما التعرف على الكلام والتعرف على المتكلم، حيث تعد عمليات التعرف هذه من أهم التقنيات الحديثة وقد تم تطوير العديد من الأنظمة التي تختلف بالطرق المستخدمة في استخراج السمات وطرق التصنيف لتدعم أنظمة تعرف من هذا النوع.اشتملت الدراسة في هذا البحث على القسمين السابقين، حيث تم تصميم نظام تعرف على المتكلم وأوامره الصوتية واستخدام عدة خوارزميات متكاملة لإنجاز البحث. قمنا بإجراء دراسة تحليلية لخوارزميةMel Frequency Cepstral Coefficients ((MFCC المستخدمة في استخراج السمات، وتمت دراسة بارامترين خاصين بهذه الخوارزمية هما عدد المرشحات في بنك المرشحات وعدد السمات المأخوذة من كل إطار وعلاقة هذين البارامترين ببعضهما ومدى تأثير قيمتهما على نسب التعرف. وتم استخدام الشبكات العصبية ذات التغذية الأمامية والانتشار الخلفي للخطأ Forwarding back propagation Neural Networks (FFBPNN)Feed كمصنف وحللنا أداء الشبكة للوصول إلى أفضل خصائص ومكونات محققة عملية التعرف. كما تمت دراسة خوارزمية Endpoint المستخدمة لإزالة فترات الصمت وتأثيرها في نسب التعرف على الصوت.Voice recognition includes two basic parts: speech and speaker recognition. These recognition processes consider as the most important processes of modern technologies, many systems has been developed that differ in the methods used to extract features and classification ways to support recognition systems of this type.The study was conducted in this research on the previous subject, where the system is designed to recognize the speaker and his voice orders and focus on several complementary algorithms to carry out the research. we conducted an analytical study on MFCC algorithm used in the extraction of features, and it has been studying two parameters the number of filters in the filters bank and the number of features that taken from each frame and the impact of these two parameters in the recognition rate and the relationship of these two parameters on each other. It was the use of feed forwarding back propagation neural networks performance analysis as characteristics and we analyze the performance of the network to gain access to the best features and components to the process of achieving recognition. And it has been studying Endpoint algorithm that used to remove periods of silence and its impact on voice recognition rates.